Characterizing the kinetic of browning index, total chlorophyll and total phenolic content of clinacanthus nutans extract - Muhammad Syafiq Sani (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Clinacanthus nutans is well known for a long time for being used as traditional medicine in Malaysia to treat skin rashes, venomous insect bite and fever. Due to the benefits of this plant, a few manufacturer starts to commercialize this plant by producing numbers of product such as extract, juice and herbal drinks (tea). It is known that many plant based food products will turn brown during thermal processing due to non-enzymatic reactions. Thermal degradation kinetics of browning index, total chlorophyll and total phenolic content in C. nutans extract was investigated at varying levels of processing temperature (40--90 C) and retention time (0-120 min). Both browning index and total chlorophyll content followed first-order reaction kinetics while total phenolic content is zero order. In browning index, overall respective coefficient of determination (R2) is 0.9237 while the activation energy is 1.6629 10-3 Jmol-1. While for kinetic of total chlorophyll the respective coefficient of determination (R2) is 0.8808 and the activation energy is 3.3256 10-3 Jmol-1. For total phenolic content the R2 is 0.9543 is and the activation energy of 8.314 10-4 Jmol-1. It is concluded that the optimization condition for thermal treatment of C. nutans extract at 55 C is best for retaining total chlorophyll content and total phenolic content and at 71.7 C it is best for preserving green color of C. nutans and total phenolic content. Results indicated that, the browning is increase due to chlorophyll degradation in C. nutans during thermal processing while Total phenolic content value increase at elevated temperature.